2019
DOI: 10.1200/jco.19.00647
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Standard Adjuvant Chemotherapy Regimens Versus Capecitabine in Older Women With Early Breast Cancer: 10-Year Update of the CALGB 49907 Trial

Abstract: PURPOSE Older women with breast cancer remain under-represented in clinical trials. The Cancer and Leukemia Group B 49907 trial focused on women age 65 years and older. We previously reported the primary analysis after a median follow-up of 2.4 years. Standard adjuvant chemotherapy showed significant improvements in recurrence-free survival (RFS) and overall survival compared with capecitabine. We now update results at a median follow-up of 11.4 years. PATIENTS AND METHODS Patients age 65 years or older with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
1
71
0
Order By: Relevance
“…There were five [ 14 , 17 19 , 21 ] and four [ 15 , 16 , 20 , 22 ] studies involving the addition or replacement of capecitabine to neoadjuvant or adjuvant chemotherapy, respectively. From the available data of TNBC, there were 1373 capecitabine combined and 1356 capecitabine-free cases in the group with the addition of capecitabine, and 384 capecitabine combined and 357 capecitabine-free cases in the group with the replacement of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were five [ 14 , 17 19 , 21 ] and four [ 15 , 16 , 20 , 22 ] studies involving the addition or replacement of capecitabine to neoadjuvant or adjuvant chemotherapy, respectively. From the available data of TNBC, there were 1373 capecitabine combined and 1356 capecitabine-free cases in the group with the addition of capecitabine, and 384 capecitabine combined and 357 capecitabine-free cases in the group with the replacement of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
“…There were seven [ 14 19 , 21 , 22 ] and one [ 20 ] studies that used capecitabine as adjuvant and neoadjuvant chemotherapy, respectively, and one study that used capecitabine as both neoadjuvant and adjuvant chemotherapy [ 19 ]. From the available data of TNBC, there were 1757 cases of adjuvant chemotherapy with capecitabine and 1713 cases of adjuvant chemotherapy without capecitabine, along with 448 cases of neoadjuvant chemotherapy with capecitabine and 428 cases of neoadjuvant chemotherapy without capecitabine.…”
Section: Resultsmentioning
confidence: 99%
“…The 10-year update of the CALBG 49907 trial confirmed the superiority of standard adjuvant chemotherapy in improving BCSS and recurrence-free survival, but no significant improvement was found in OS, probably due to competing risks of death diluting the benefit in an older population. 30 The follow-up trial also used modest chemotherapy regimens (ie, four courses of doxorubicin and cyclophosphamide or six courses of CMF).…”
Section: Discussionmentioning
confidence: 99%
“…However, no evidence of significantly improved five-year OS was observed for patients allocated to the intervention arm (HR, 0.74, p = 0.203) [ 30 ]. Even though results from clinical trials regarding the implementation of capecitabine in early TNBC were not always consistent [ 31 , 32 , 33 ], routine clinical care of TNBC not achieving pCR after neoadjuvant chemotherapy often embraces adjuvant treatment with capecitabine. Moreover, a recent meta-analysis presented at the 2019 San Antonio Breast Cancer Symposium highlighted more pronounced, significant benefits in terms of DFS and OS from the addition of capecitabine to neoadjuvant chemotherapy in the TNBC subtype [ 34 ].…”
Section: Resultsmentioning
confidence: 99%